Introducing Indonesia’s Cultural Diversity through Technology: Traditional Attire Education for Elementary Schools - Ageng Satria Pamungkas; Nur Innayah Ganjarjati (PT. Anagata Sembagi Education, 2024)
This research explores the effectiveness of using technology as a medium for introducing the cultural heritage of traditional Indonesian attire to elementary school students. Cultural education plays an essential role in shaping students' identities and fostering an appreciation for Indonesia’s rich diversity from an early age. Traditional lecture-based methods, which are often limited to textbooks, tend to be less engaging and struggle to deepen students’ understanding. Therefore, there is a need for innovative approaches that leverage technology to create a more interactive and contextual learning experience. The study employs a literature review from academic articles, books, and reports on the use of technology in cultural education. The findings indicate that the use of three-dimensional imagery, videos, and interactive multimedia significantly enhances student interest and comprehension of traditional attire. These technological tools provide visually engaging representations, enabling students to grasp the meaning and cultural significance embedded in traditional clothing elements through a richer and more immersive learning experience. This research contributes to the development of technology-based educational resources for cultural studies in elementary schools, highlighting the importance of technological innovation in cultural education. Integrating technology into cultural learning offers an effective approach for introducing students to Indonesia’s diverse traditional attire, thus enriching their cultural understanding and engagement.